The Path and Enlightenment of Data-Driven Digital Transformation of Organizational Learning ——A Case Study of the Practice of China Telecom - Siyuan Xu; Wenhao Yu; Guanghua Jiang (Adult Education Research Conference, 2023)
This paper took China Telecom as a case. It has analyzed data-driven digital transformation in organizational learning, and summarized the methods and enlightenments of digital transformation.
Keywords: digital transformation; organizational learning; data-driven; China Telecom